Advances in the metal nanoparticles (MNPs) doped liquid crystals and polymer dispersed liquid crystal (PDLC) composites and their applications - a review. Issue 1 (12th December 2021) - Ahmad, Farzana; Luqman, Mohammad; Jamil, Muhammad
Abstract: There is a great interest in doping of different types of nanoparticles (NPs) in the opto-electronic display devices including liquid crystal displays and polymer dispersed LCs. Doping of NPs into the LC displays improves EO characteristics of the films including low threshold voltage, and alterations in pretilt angle. Specifically, gold NPs (GNPs) doped PDLC films demonstrate superior EO and dielectric characteristics. The article extensively explores recent experimental progress and technical issues related to the dispersion of GNPs into the LCs i.e., tuning of LC properties with doping of GNPs. Some recent advances of GNP doped PDLCs have been briefly discussed.